Two responsa of R. Samson Morpurgo on non-kosher medicines Therapy vs. Jewish Halakic Principles - Shemesh, Avraham Ofir 1966- (2019)
In the eighteenth-century Europe, medical practices often still followed theories originating from classical and medieval medicine. In addition, medicaments produced from plants, minerals, or animals, such as snake meat, were commonly used to treat a wide range of illnesses. This study addresses the approach of the Jewish-Italian physician R. Samson Morpurgo (1681-1740) to the use of non-kosher medications. According to Morpurgo's outlook, providing the patient with proper medical care and consideration for the dictates of halakha are two intertwined and interrelated aspects. The condition of a patient whose life is in danger might have the effect of reducing the halakhic restrictions while, on the other hand, halakha has the power to determine or intervene in manners of treating patients whose life is not in danger. Sometimes the authority of Jewish law and medical needs clash and form a moral-religious conflict. In such cases, Morpurgo is of the opinion that preference should be given to halakha, although in some cases the need for medical action has the upper hand and overrides the restrictions posed by Jewish law, as ultimately the patient's health is valued above all else.
Keywords: Abi'ad Sar Shalom Basilea of Mantua; Italian Jews; Jewish medicine; Jewish physicians; Samson Morpurgo; hydroken; kosher remedies; snake medicine; stam yeinam; theriac